On the Comprehensibility of EU Legislation: Reform for a sustainable EU - Xanthaki, Helen (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2021)
EU legislation is currently speaking to EU institutions, and Member States and their national authorities. It is therefore detached from EU citizens. Enhancing the comprehensibility of EU legislation can forge a direct channel of communication between the EU and its citizens, thus strengthening their trust and loyalty to the organization and its ideals. This can nurture sustainable integration for the longevity and prosperity of the EU.